Characterization of the membrane interactions of phospholipase Cgamma reveals key features of the active enzyme - Le Huray, K. I. P.; Bunney, T. D.; Pinotsis, N.; Kalli, A. C.; Katan, M. (Sci AdvSci Adv, 2022)
PLCgamma enzymes are autoinhibited in resting cells and form key components of intracellular signaling that are also linked to disease development. Insights into physiological and aberrant activation of PLCgamma require understanding of an active, membrane-bound form, which can hydrolyze inositol-lipid substrates. Here, we demonstrate that PLCgamma1 cannot bind membranes unless the autoinhibition is disrupted. Through extensive molecular dynamics simulations and experimental evidence, we characterize membrane binding by the catalytic core domains and reveal previously unknown sites of lipid interaction. The identified sites act in synergy, overlap with autoinhibitory interfaces, and are shown to be critical for the phospholipase activity in cells. This work provides direct evidence that PLCgamma1 is inhibited through obstruction of its membrane-binding surfaces by the regulatory region and that activation must shift PLCgamma1 to a conformation competent for membrane binding. Knowledge of the critical sites of membrane interaction extends the mechanistic framework for activation, dysregulation, and therapeutic intervention.
Le Huray, Kyle I PBunney, Tom DPinotsis, NikosKalli, Antreas CKatan, MatildaengMC_PC_MR/T032774/1/MRC_/Medical Research Council/United KingdomMR/P028160/1/MRC_/Medical Research Council/United KingdomSci Adv. 2022 Jun 24;8(25):eabp9688. doi: 10.1126/sciadv.abp9688. Epub 2022 Jun 24.
Keywords: *Lipids; *Signal Transduction; Catalytic Domain